ESR dating of late Quaternary megafauna fossils from João Dourado, Bahia, Brazil. (August 2020) - Faria, Fabio Henrique Cortes; Kinoshita, Angela; Carvalho, Ismar de Souza; Araújo-Júnior, Hermínio Ismael de; Pegorin, Priscila; Maria G Figueiredo, Ana; Baffa, Oswaldo
Abstract: We applied the ESR (Electron Spin Resonance) dating method to fossils of Notiomastodon platensis (two teeth) and Toxodontinae (two teeth) found in the fossiliferous deposit of Lajedão do Patrício, João Dourado, State of Bahia, Brazil, to identify the period of formation of this fossil accumulation. Neutron Activation Analysis was applied to determine the concentrations of the main radioisotopes in enamel, dentine and sediment. The ages found for N. platensis are 16.8 ± 2.6 ka and 12.5 ± 2.3 ka, while the ages for Toxodontinae are 9.6 ± 1 ka and 9.1 ± 1 ka. The results for Notiomastodon. platensis and Toxodontinae are similar to other fossiliferous of Brazil. The estimated maximum time-averaging for Lajedão do Patrício is 11.3 ka, indicating a long period of accumulation of skeletal remains, attributed to resedimentation and reworking. The crossing between the period of formation of fossil assemblage Lajedão do Patrício and ages of climatic variations diponible in paleoclimatic curves produced for the Quaternary of northeastern Brazil indicates different climatic and environmental conditions during the formation of the deposit. Highlights: Dating Electron Spin Resonance (ESR) Notiomastodon platensis and Toxodontiane from the Quaternary of Northeast Brazil. Notiomastodon platensis are 16.8 ± 2.6 ka and 12.5 ± 2.3 ka, and Toxodontinae 9.6 ± 1 ka and 9.1 ± 1 ka. Maximum time-averaging for Lajedão do Patrício is 11.3 ka, indicating a long period of accumulation . Comparison of Lajedão do Patrício and paleoclimatic curves different climatic and environmental conditions.